2020
DOI: 10.1101/2020.07.14.203414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bivalent binding of a fully human IgG to the SARS-CoV-2 spike proteins reveals mechanisms of potent neutralization

Abstract: In vitro antibody selection against pathogens from naïve combinatorial libraries can yield various classes of antigen-specific binders that are distinct from those evolved from natural infection1–4. Also, rapid neutralizing antibody discovery can be made possible by a strategy that selects for those interfering with pathogen and host interaction5. Here we report the discovery of antibodies that neutralize SARS-CoV-2, the virus responsible for the COVID-19 pandemic, from a highly diverse naïve human Fab library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…We characterized Fab-S cryo-EM structures (overall resolutions from 3.4-3.8Å) of potent hNAbs (C002, C104, C119, and C121) predicted to compete with ACE2 binding 5 , which varied in their V gene segment usage and CDRH3 lengths ( Table 1). Fab-S cryo-EM structures of these class 2 hNAbs showed bound RBDs in both "up" or "down" conformations, consistent with observations of similar hNAbs from nsEM 5,12 and single-particle cryo-EM studies 10,34,41 . By contrast, the C144-S structure showed Fabs bound only to "down" RBDs ( Fig.…”
Section: Articlesupporting
confidence: 83%
“…We characterized Fab-S cryo-EM structures (overall resolutions from 3.4-3.8Å) of potent hNAbs (C002, C104, C119, and C121) predicted to compete with ACE2 binding 5 , which varied in their V gene segment usage and CDRH3 lengths ( Table 1). Fab-S cryo-EM structures of these class 2 hNAbs showed bound RBDs in both "up" or "down" conformations, consistent with observations of similar hNAbs from nsEM 5,12 and single-particle cryo-EM studies 10,34,41 . By contrast, the C144-S structure showed Fabs bound only to "down" RBDs ( Fig.…”
Section: Articlesupporting
confidence: 83%
“…Our biochemical and cell-based experimental results showed that the full-length IgG nAbs have greater binding ability, neutralization ability, and induce more S1 shedding than Fab. Similar results were also obtained in other study (27) reported, most of which used nAb in Fab-form, especially those solved with X-ray crystallography. Our results suggest that the full-length IgG-form, which is more biologically relevant than Fab, should be used for the structural determination as much as possible to understand the structural and functional features of nAbs.…”
Section: Discussionsupporting
confidence: 90%
“…To obtain pre-fusion spike ectodomain, methods similar to the previous reports were used. 33 , 49 The expression plasmid, provided by the McLellan lab, was used in a transient transfection with 100 mL, high-density Chinese Hamster Ovary (ExpiCHO, Thermo Fisher) culture following the “High Titer” protocol provided by Thermo Fisher. Six to nine days post-transfection, the supernatant was collected with centrifugation at 4,000xg at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain pre-fusion spike ectodomain, methods similar to the previous reports were used. 33,49 The processing package. 51 Micrographs were manually curated, CTF was estimated utilizing patches and particles were picked with a Gaussian blob.…”
Section: Expression and Purification Of Spike Ectodomain For Cryo-emmentioning
confidence: 99%